Sasanian seals in Hungarian collections - Gesztelyi, Tamás (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
There are relatively few Sasanian seals in the Hungarian archaeological collections, and there is only one that was found in Hungary. Their review has been made timely by the appearance of a few pieces in the art trade. One of their characteristic motifs is the resting ram, but resting griffin and a winged szphinx also appear as motifs.